Recent advances and strategies for high-performance coatings - Ou, Y.X.; Wang, H.Q.; Ouyang, X.; Zhao, Y.Y.; Zhou, Q.; Luo, C.W.; Hua, Q.S.; Ouyang, X.P.; Zhang, S. (Progress in materials science, 2023)
Coatings with micro- or nano-scaled structure are always fabricated by various techniques to fulfill the requirements of unique performances according to special working conditions. The differences in preparation techniques always result in large differences in their properties, even for the same coating materials. High-performance coatings are solely up to surface integrity, morphology, microstructure, stress state, interfacial structure, cohesion and adhesion that are all strongly affected by preparation processes. Therefore, how to take advantage of the numerous deposition techniques to design a right preparation process to produce coatings of high performance to meet the demands is the real question. This work set out to answer this question. We first discuss the overall strategies towards making of high-performance coatings including deposition techniques, coatings and characterizations. We then move on to superior performances and durability of protective coatings and functional coatings. These strategies are readily applicable in making of various high-performance protective and functional coatings.